Smart prepaid energy metering system to detect energy theft with facility for real time monitoring - Somefun T. E; Awosope C.O.A; Chiagoro A. (Institute of Advanced Engineering and Science, 2019)
Electricity theft remains a huge loss incurred by electricity distribution companies. This theft arises majorly because of activities carried out by consumers such as energy-meter by-passing, energy-meter tampering etc. This research study offers an approach for handling energy meter by-passing and tampering. The system design is based on the monitoring of the readings of two current sensors by a programmed microcontroller. While one of the current sensors monitors the current drawn by the user’s load, the latter installed before the meter monitors current drawn by all loads. Any discrepancy between the values read, indicates theft. A momentary switch is also installed in the meter to trigger the meter once it is tampered with. Furthermore, the user is provided with a remote access to the energy meter for recharging energy units and for monitoring energy consumption. It was observed that the system accurately measured load consumption and detect any attempt to by-pass or tamper with the energy meter. Lastly, all unscrupulous attempts were reported using GSM technology.